ZAMONAVIY O‘ZBEK BADIIY KINOSIDA OPERATORLIK USLUBLARINING RIVOJLANISHI (SUBYEKTIV KAMERA) (ART AND CULTURE BULLETIN, 2025)
The article analyzes the development of cinematographic styles in Uzbek feature filmsthrough the example of the subjective camera. I. Lutfullayevʼs visual styles are examined from an art studiesperspective, exploring their dramaturgical function, expressive potential, and system of visual imagery.
Keywords: cinematography; technological progress; digital technologies; image a esthetics; expressive tools; traditional and modern approach.